1994
DOI: 10.1039/ja9940900177
|View full text |Cite
|
Sign up to set email alerts
|

Spectral interferences encountered in the analysis of biological materials by inductively coupled plasma mass spectrometry

Abstract: In order to evaluate the potential of inductively coupled plasma mass spectrometry for the analysis of biological materials, a systematic study on the occurrence of spectral interferences was carried out. All polyatomic ions originating from the matrix elements Ca, Cl, P, K, C, Na and S that give rise to spectral overlap with the analyte elements were examined systematically. For these matrix elements, which are representative of most biological materials, a list of all the polyatomic ions, which can be seen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…9 However, the formation of molecular species in the plasma, such as Ar ) that cause isobaric interferences may worsen precision and accuracy. [10][11][12] Additionally, the formation of oxides can also deteriorate the sensitivity for elements such as U, Ba and lanthanides. 13,14 It is worth citing that the conditions of operation of the instrument, the instrument type and quality of aerosol introduced into the plasma influence the formation of molecular species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 However, the formation of molecular species in the plasma, such as Ar ) that cause isobaric interferences may worsen precision and accuracy. [10][11][12] Additionally, the formation of oxides can also deteriorate the sensitivity for elements such as U, Ba and lanthanides. 13,14 It is worth citing that the conditions of operation of the instrument, the instrument type and quality of aerosol introduced into the plasma influence the formation of molecular species.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the formation of oxide and hydroxides ions is drastically reduced. 12,15 In addition, the limits of detection (LODs) are better (typically in one order of magnitude) because more sample is transported to the plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeable interference was found for Ge, As and Se, showing that below m/z = 85 the background spectrum is not free of interference peaks. [27][28][29] Moreover, at m/z = 70-82, interference from oxides or argon dimer ion ( …”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Oliver et al 9) and Tan et al 10) reported the matrix effect in ICP-MS in detail, and it was found that errors resulted from the mutual relationship between the atomic numbers of analyzed and matrix elements and ionization potential. In urine samples, relatively light elements such as C, P, S, and Cl may serve as matrices.…”
Section: Interference By Sodium Chloridementioning
confidence: 99%